Urgensi Media Animasi Moderasi Beragama dalam Pembelajaran Pendidikan Agama Islam pada Pesantren di Indonesia - AR, Samsul; Fauzan, Fauzan (Al-Abshar: Journal of Islamic Education Management, 2024)
Learning media serve as a bridge to convey messages between educators and students. Learning media play a strategic role in providing a holistic understanding of the content within Islamic religious education materials. One of the essential learning media that Islamic education teachers should utilize is animation-based media on religious moderation. This medium is crucial for educators to effectively deliver the values of religious moderation in textual form to students through animated media. Animation media can convey messages both visually and audibly, enabling students to easily understand, imitate, and apply them in their daily lives. This study highlights the urgency of using animation media in Islamic religious education learning in Islamic boarding schools (pesantren), where the teaching process is traditionally conducted through lectures, bandongan, wetonan, and sorogan methods. It also discusses the supporting factors for the implementation of animation-based media on religious moderation in Islamic religious education learning at pesantren. This article utilizes a library research method with a disruptive analysis approach. Data were collected through the review of various documents, including journals, books, and similar sources. The findings indicate that Islamic religious education at pesantren is traditionally taught using lecture-based methods. However, animation media has the potential to motivate students in pesantren to emulate the concepts depicted in Islamic education animation. Pesantren hold significant potential for adopting animation media in the learning process of Islamic religious education. So the contribution of this research is as a development of the use of animation-based Islamic religious education learning media to motivate students in studying at Islamic boarding schools in Indonesia.